Negotiating Religious Values and Relational Needs: The Dynamics of Dating Decision-Making among Islamic Boarding School Students - Faliha Muthmainah; Nurul Adila Alfatiha (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Dating is generally considered inconsistent with the values and regulations upheld in Islamic boarding schools. Nevertheless, some students choose to engage in romantic relationships despite being aware of these restrictions. This study aimed to explore the dynamics of dating decision-making among Islamic boarding school students within the context of negotiating religious values and relational needs. A phenomenological approach was employed involving six adolescents aged 16–17 years who were currently or had previously been involved in dating relationships. Data were collected through in-depth interviews and observations and were analyzed using Interpretative Phenomenological Analysis. The findings revealed that dating decisions emerged through a complex negotiation process involving religious beliefs, relational needs, personal experiences, and social influences. The need for affection, emotional support, and interpersonal closeness encouraged students to pursue romantic relationships, while religious values and boarding school regulations generated ongoing psychological conflicts. Peer influence, family background, social media exposure, and previous romantic experiences also shaped how students interpreted and maintained their decisions. These findings suggest that dating among Islamic boarding school students was not merely an act of norm violation but rather the result of a dynamic decision-making process in response to competing value systems and developmental needs during adolescence.